Perancangan Sistem Akuntansi Persediaan Dan Kartu Gudang Berbasis Komputer Pada Konveksi Tas - Endrawati; Surya, Firman; Putra Perta R., Widio (Akuntansi dan Manajemen, 2015)
Bag is one of commodities produced by local industries in Indonesia in general, and in particular western Sumatra. However, the company, has several weaknesses related to the management and recording of inventory such as the lack of segregation of duties and responsibilities by each section, management procedures and record-keeping supplies inadequate and the lack of documents and records that support the transactions related to inventory , This research aims to design a card inventory accounting system and computer-based warehouse that will be applied to the sales system, purchasing system and system of material usage to fit the elements contained in the internal control system. Based on research that has been done, then the inventory accounting system designed in accordance with the elements contained in the internal control systems and computer-based warehouse cards are useful for recording the transfer of inventory stored in warehouse. Besides being able to produce information that is far more accurate than manual recording, computer-based warehouse card is also used in the savings and effectiveness of the use of the document processing time.